Prevalence of chronic non-communicable diseases in Ethiopia: A systematic review and meta-analysis of evidence - Tesfay, Fisaha Haile; Zorbas, Christina; Alston, Laura; Backholer, Kathryn; Bowe, Steven J.; Bennett, Catherine M. (Frontiers in Public Health, 2022)
Background: Noncommunicable diseases (NCDs) are a growing global health challenge disproportionately impacting low- and middle-income settings, including Ethiopia. Currently, the body of evidence describing the burden of NCDs is fragmented, inconsistent, health facility- or institution-based, and out-dated in Ethiopia. We conducted a systematic review of the literature and meta-analysis of the prevalence of NCDs in community settings in Ethiopia. Review methodology: Community-based quantitative studies published in English between January 1st, 2012, and June 30th, 2022, that reported on the prevalence of NCDs in Ethiopia were included. A systematic search of Medline, Embase, Scopus, CINAHL, and Global Health using pretested search terms was conducted, and data were extracted using data extraction proforma adapted from the Joanna Briggs Institute tool. Meta-analysis was performed using Stata 16. While the pooled prevalence of Diabetes Mellitus (DM) and undiagnosed (DM) was computed and presented using forest plots, and overall prevalence of NCDs and other various types of NCDs were narratively synthesised. I2 was used to assess heterogeneity. Results: Nineteen studies met the inclusion criteria. Four studies measured the prevalence of NCDs (all NCDs together), ranging from 29% to 35% (prevalence estimates not pooled). The pooled prevalence of Diabetes Mellitus (DM) across ten studies was 5% (95% CI:4%−7%). Three studies each reported on the prevalence of undiagnosed DM (pooled prevalence 5%, 95% CI: 4%−7%) and pre-DM (pooled prevalence 7%, 95% CI:3%−14%%). In a narrative analysis the prevalence of cardiovascular conditions ranged from 13.4% to 32.2% (n=3 studies), cancer mortality ranged from 4% to 18% (n= 3 studies) and respiratory conditions ranged from 1% to 18% (n=3 studies). Conclusion and recommendations: Our analysis found that approximately one-third of Ethiopians have an NCD, with cardiovascular diseases the most common of all NCDs. The prevalence of respiratory conditions also appears high, but there are insufficient data for a pooled estimate. Whilst the prevalence of DM appears relatively low, there is evidence that the magnitude is increasing. Public health actions to address the high burden of cardiovascular and respiratory diseases, as well as the increasing magnitude of DM in Ethiopia, must be prioritised.